OPTIMIZING SOCIAL MEDIA STRATEGIES TO ENHANCE CUSTOMER ENGAGEMENT: A CASE STUDY OF PT ICONNET (ICON+) - Almira, Nasywa; Siregar, Suci; Nurlina Nasution; Arya Advany (Politeknik Ubaya, 2025)
In today’s rapidly evolving digital landscape, social media has become a crucial tool for businesses seeking to build lasting relationships with their customers. This study investigates the role of social media in enhancing customer engagement at PT ICONNET (ICON+), a broadband internet service provider and subsidiary of PT PLN, amidst the fierce competition in Indonesia’s telecommunications market. Despite having strong infrastructure support from PLN, PT ICONNET faces significant challenges in optimizing its social media strategies, which impacts customer interaction and loyalty. Through a descriptive qualitative approach, including interviews, observations, and document analysis, this research identifies both the internal and external factors that influence the company’s social media effectiveness. The findings highlight the strengths of PT ICONNET, such as its reliable infrastructure and public sector reputation, but also reveal key weaknesses, including slow decision-making, inconsistent content strategy, and evolving social media algorithms. Based on SWOT, IFAS, and EFAS analyses, the study proposes strategies for improving engagement, such as content optimization, leveraging new social media features, and enhancing the digital team's capabilities. Given the urgency of adapting to the digital demands of today’s consumers, the study concludes that PT ICONNET must adopt a more data-driven and adaptive social media strategy. This will help the company foster stronger customer connections, improve brand loyalty, and solidify its competitive edge in Indonesia’s dynamic ISP industry.